Transcranial Magnetic Stimulation in Autism Spectrum Disorders: Neuropathological Underpinnings and Clinical Correlations - Casanova, Manuel F. (Semin Pediatr Neurol, 2020)
Despite growing knowledge about autism spectrum disorder (ASD), research findings have not been translated into curative treatment. At present, most therapeutic interventions provide for symptomatic treatment. Outcomes of interventions are judged by subjective endpoints (e.g., behavioral assessments) which alongside the highly heterogeneous nature of ASD account for wide variability in the effectiveness of treatments. Transcranial magnetic stimulation (TMS) is one of the first treatments that targets a putative core pathological feature of autism, specifically the cortical inhibitory imbalance that alters gamma frequency synchronization. Studies show that low frequency TMS over the dorsolateral prefrontal cortex (DLPC) of individuals with ASD decreases the power of gamma activity and increases the difference between gamma responses to target and non-target stimuli. TMS improves executive function skills related to self-monitoring behaviors and the ability to apply corrective actions. These improvements manifest themselves as a reduction of stimulus bound behaviors and diminished sympathetic arousal. Results become more significant with increasing number of sessions and bear synergism when used along with neurofeedback. When applied at low frequencies in individuals with ASD, TMS appears to be safe and to improve multiple patient-oriented outcomes. Future studies should be conducted in large populations to establish predictors of outcomes (e.g., genetic profiling), length of persistence of benefits, and utility of booster sessions.